Solution to Overcome Import Tariff Barriers for Vietnamese Goods Exported to the European Union Market (International Journal of Scientific Research and Management (IJSRM), 2023)
The research aims to propose solutions for overcoming non-tariff barriers in the export of Vietnamese goods to the European Union (EU) market. The study identifies common characteristics within the bloc, using data collected from 2015 to 2022. Various methods such as statistical analysis, balance analysis, interpretation, deduction, synthesis analysis, logic methods, and forecasting were employed. Based on the research findings, the author suggests several groups of solutions to address non-tariff barriers when exporting goods to the EU market: Government-related solutions (Enhancing information dissemination, promoting EU trade laws and policies; Proactively addressing anti-dumping barriers); Association-related solutions (Improving information collection and processing capabilities; Willingness to litigate and counter-litigate); Legal consulting organizations’ solutions; Business-related solutions; Solutions for the seafood industry; Solutions for the footwear industry; Solutions for the textile and garment industry.